Relationships Between Work-to-Family Conflict and the Food Domain for Dual-Earner Parents With Adolescent Children - Schnettler, Berta; Miranda-Zapata, Edgardo; Orellana, Ligia; Poblete, Héctor; Lobos, Germán; Adasme-Berríos, Cristian; Lapo, María; Beroiza, Katherine (Frontiers in Psychology, 2021)
The impact of work-to-family conflict (WtoFC) can extend beyond family and work, and to other domains that contribute to well-being, such as the food domain. This study examined associations between WtoFC, perception of atmosphere of family meals (AFM), and satisfaction with food-related life (SWFoL) in dual-earner parents with adolescent children, and tested the mediating role of AFM between WtoFC and SWFoL. Questionnaires were administered to 473 different-sex dual-earner parents and one of their adolescent children (mean age 12.5 years, 51.4% male) in Temuco, Chile. Parents responded to a measure of work-to-family conflict; the three family members answered the Project-EAT Atmosphere of family meals scale, and the Satisfaction with Food-related Life Scale. Analyses were conducted using the Actor-Partner Interdependence Model and structural equation modelling. Results showed a negative association from WtoFC to SWFoL in both parents, while a more positive perception of atmosphere of family meals was linked to higher SWFoL in the three family members. Moreover, WtoFC was negatively linked to SWFoL in parents, while only mothers’ WtoFC had a negative association with their adolescent children’s SWFoL. Policymakers and organizations can contribute to workers’ and their families’ food-related well-being by fostering policies and measures to reduce WtoFC.